2017
DOI: 10.26694/reufpi.v6i1.5737
|View full text |Cite
|
Sign up to set email alerts
|

(Des) preparation of family member for the care of children with chronic illness / (Des)preparo do familiar para o cuidado à criança com doença crônica / (Des) la preparación de la familia para el cuidado de los niños con enfermedades...

Abstract: Objetivo: conhecer como ocorre o preparo da família para o cuidado à criança com doença crônica. Metodologia: pesquisa qualitativa realizada Pediatria de um hospital universitário do sul do Brasil. Entre janeiro e dezembro de 2013 se realizou as entrevistas com 15 familiares cuidadores de crianças internadas com doenças crônicas, foram tratadas pela análise temática. Resultados: identificaram-se duas categorias, o processo de preparo da família para o cuidado à criança com doença crônica e (Re)organização fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
4
0
5
Order By: Relevance
“…É imprescindível construir modelos que primem pela autonomia dos sujeitos, pela afirmação dos princípios de cidadania e democracia, evidenciando o compromisso social com a melhoria do estado de saúde da população. Logo, urge pensar a promoção da saúde como marco conceitual no redirecionamento do processo ensinoaprendizagem dos profissionais de saúde e de enfermagem (20) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…É imprescindível construir modelos que primem pela autonomia dos sujeitos, pela afirmação dos princípios de cidadania e democracia, evidenciando o compromisso social com a melhoria do estado de saúde da população. Logo, urge pensar a promoção da saúde como marco conceitual no redirecionamento do processo ensinoaprendizagem dos profissionais de saúde e de enfermagem (20) .…”
Section: Resultsunclassified
“…Além disso, observa-se que a complexidade dos problemas ambientais clama pela adoção de medidas que superem práticas assistencialistas, contribuindo, assim, para práticas transdisciplinares, e, portanto, o enfermeiro educador deve, juntamente com outros agentes da sociedade, intentar modificar o cenário que o cerca (20) . ISSN: 2238-7234 Beserra EP, et al…”
Section: Resultsunclassified
“…Also noteworthy is the recent discovery about the association of microcephaly with Zika virus infection, which, in the female caregivers' imagination, represents something incapacitating and difficult to overcome. 4,8 In the second subgroup under analysis, it is pointed out that the term "prenatal", being close to the words "discover", "pregnancy" and "nurse", demonstrates that, for these women, prenatal is related to apprehension, as it is critical for Zika virus infection. It is understood that the term "nurse" reveals the consultations performed by this professional and its importance in monitoring and guidance on diagnostic tests to confirm contamination and the occurrence of microcephaly in their children.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that this phenomenon generates a social stigma according to which the female caregiver should believe that only she is capable and responsible for the integral attention to the child, especially in the conditions of chronic illness, as happens in microcephaly. 3,8 Health professionals are defined as indispensable for breaking negative social constructs, which place on women, mothers and female caregivers the unique burden of family care. It is suggested that the nurse, in providing care to families affected by microcephaly, should promote a detailed dialogue on this condition, individually, in order to explain its complications, clinical condition, consequences, necessary care and involvement of the woman's social network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation